Effectiveness of Junior High Schools in Minahasa Regency - Hansje Tommy Wuwungan; Herry Sumual; Rolles N. Palilingan; Henny Nikolin Tambingon (JR Education, 2026)
This study aims to analyze the effectiveness of junior high schools (SMP) in Minahasa Regency and to examine the influence of teacher competence, learning resource management, instructional media, principal leadership, classroom management, and school academic culture on school effectiveness. This research employed a quantitative approach using a survey method. The study was conducted in 103 public and private junior high schools in Minahasa Regency. Data were collected through questionnaires, observations, and documentation, involving teachers and principals as respondents. Data analysis was performed using multiple linear regression, preceded by classical assumption tests including normality, linearity, and multicollinearity tests, with a significance level of α=0.05. The results show that, partially, teacher competence, learning resource management, instructional media, principal leadership, classroom management, and school academic culture have a positive and significant effect on junior high school effectiveness in Minahasa Regency, with significance values of p < 0.05 for each variable. Simultaneously, the results of the F-test indicate that the six independent variables jointly have a significant effect on school effectiveness (Sig. < 0.05). Furthermore, the coefficient of determination indicates that school effectiveness is substantially influenced by the combined contribution of these variables, while the remaining variance is explained by other factors outside the research model. The study concludes that the effectiveness of junior high schools in Minahasa Regency is significantly influenced by teacher competence, learning resource management, instructional media, principal leadership, classroom management, and school academic culture, both partially and simultaneously. Therefore, improving school effectiveness requires an integrated and sustainable strengthening of these factors to enhance educational quality and achieve optimal educational outcomes at the junior high school level.